Cost Effectiveness of Pneumococcal Conjugate Vaccination against Acute Otitis Media in Children: A Review - Boonacker, Chantal W.B.; Broos, Pieter H.; Sanders, Elisabeth A.M.; Schilder, Anne G.M.; Rovers, Maroeska M. (PharmacoEconomics, 2011)
While pneumococcal conjugate vaccines have shown to be highly effective against invasive pneumococcal disease, their potential effectiveness against acute otitis media (AOM) might become a major economic driver for implementing these vaccines in national immunization programmes. However, the relationship between the costs and benefits of available vaccines remains a controversial topic. Our objective is to systematically review the literature on the cost effectiveness of pneumococcal conjugate vaccination against AOM in children. We searched PubMed, Cochrane and the Centre for Reviews and Dissemination databases (Database of Abstracts of Reviews of Effects [DARE], NHS Economic Evaluation Database [NHS EED] and Health Technology Assessment database [HTA]) from inception until 18 February 2010. We used the following keywords with their synonyms: ‘otitis media’, ‘children’, ‘cost-effectiveness’, ‘costs’ and ‘vaccine’. Costs per AOM episode averted were calculated based on the information in this literature. A total of 21 studies evaluating the cost effectiveness of pneumococcal conjugate vaccines were included. The quality of the included studies was moderate to good. The cost per AOM episode averted varied from €168 to €4214, and assumed incidence rates varied from 20952 to 118000 per 100000 children aged 0–10 years. Assumptions regarding direct and indirect costs varied between studies. The assumed vaccine efficacy of the 7-valent pneumococcal CRM197-conjugate vaccine was mainly adopted from two trials, which reported 6–8% efficacy. However, some studies assumed additional effects such as herd immunity or only took into account AOM episodes caused by serotypes included in the vaccine, which resulted in efficacy rates varying from 12% to 57%. Costs per AOM episode averted were inversely related to the assumed incidence rates of AOM and to the estimated costs per AOM episode. The median costs per AOM episode averted tended to be lower in industry-sponsored studies. Key assumptions regarding the incidence and costs ofAOMepisodes have major implications for the estimated cost effectiveness of pneumococcal conjugate vaccination against AOM. Uniform methods for estimating direct and indirect costs of AOM should be agreed upon to reliably compare the cost effectiveness of available and future pneumococcal vaccines against AOM.